Method optimization of models parameters for the nonstationary traffic in telecommunication network - Ignatov, V. O.; ZIJUAN, WU (Problems of Informatization and Control, 2008)
Results of models parameters optimization for the nonstationary traffic in telecommunication and computer networks are given. For optimum modeling of the traffic dynamics metrics of Euclid’s and Gilbert’s spaces are used. The technique and algorithm of models optimization are developed. Theoretical positions are illustrated by numerical examples and diagrams with use ofMathCAD